Translation and Cultural Adaptation of the ISTH-Bleeding Assessment Tool to European Portuguese - Diana Carneiro-Leão; Sofia Teixeira; Rita Queirós Pereira; Teresa Mota; Manuela Lopes; Susana Nobre-Fernandes; Fernando Araújo (Acta Médica Portuguesa)
Introduction: A distinctive bleeding history is the first diagnostic stage of congenital hemorrhagic diseases. Furthermore, since it is in fact an assessment of the patient’s phenotype, it is not a (mere) complementary diagnostic method or test - it is an integral and intrinsic step to establish the patient’s clinical history, which is a medical act. The International Society on Thrombosis and Haemostasis-Bleeding Assessment Tool (ISTH-BAT) is a standardized bleeding assessment tool used during the diagnostic workup of suspected bleeding disorders. This study aimed to translate and culturally adapt the ISTH-BAT questionnaire to the European Portuguese language. Methods: The translation and cultural adaptation were based on the International Society for Pharmacoeconomics and Outcomes Research Guidelines and initiated after obtaining permission from the authors. The process involved three English to European Portuguese independent forward translations and a back translation. Discrepancies were gradually resolved. A harmonized version was presented to hemophilia patients and hemophilia carriers for cognitive debriefing. Results: The forward and back translations did not produce important discrepancies. However, some issues were identified in the cognitive debriefing, which led to the cultural adaptation of medical terms for better understanding. Conclusion: A formal translation and cultural adaptation process ensures that the new version maintains the same concepts as the original. After translation, several changes were necessary to ensure that the questionnaire was understandable by non-medical patients. We propose a European Portuguese version of the ISTH-BAT, which will require validation in further studies.